Beyond Schools: Community-Based Experiences as a Third Space in Teacher Education - Melanie D. Janzen; Christie Petersen (Brock University, 2020)
Some teacher education programs have incorporated community-based experiences for teacher candidates. Based on the experiences of developing and implementing a community-based practicum in our teacher education programs, the authors conducted a small exploratory case study, aimed at examining and critically considering community-based experiences as a "third space;" an opportunity through which to challenge teacher candidates' strongly held understandings of teaching. The purposes of this article are to share our literature review, to provide some key insights from the study findings, and to explore our lingering questions regarding the development and implementation of community-based experiences and to consider the possibilities of community-based experiences as a third space in which to disrupt teacher candidates' assumptions about teaching.